Proceedings of the 43rd ACM SIGPLAN International Conference on Programming Language Design and Implementation 2022
DOI: 10.1145/3519939.3523436
|View full text |Cite
|
Sign up to set email alerts
|

Efficient approximations for cache-conscious data placement

Abstract: There is a huge and growing gap between the speed of accesses to data stored in main memory vs cache. Thus, cache misses account for a significant portion of runtime overhead in virtually every program and minimizing them has been an active research topic for decades. The primary and most classical formal model for this problem is that of Cacheconscious Data Placement (CDP): given a commutative cache with constant capacity 𝑘 and a sequence Σ of accesses to data elements, the goal is to map each data element t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…The theoretical bound of [78] does not apply to Java, but the work [44] showed that the treewidth of control-flow graphs in real-world Java programs is also bounded. This bounded-treewidth property has been used in a variety of static analysis and compiler optimization tasks to speed up the underlying algorithms [25,62,3,27,36,26,20,23,5,38,2]. Nevertheless, one can theoretically construct pathological examples with high treewidth.…”
Section: Treewidth and Treedepthmentioning
confidence: 99%
See 1 more Smart Citation
“…The theoretical bound of [78] does not apply to Java, but the work [44] showed that the treewidth of control-flow graphs in real-world Java programs is also bounded. This bounded-treewidth property has been used in a variety of static analysis and compiler optimization tasks to speed up the underlying algorithms [25,62,3,27,36,26,20,23,5,38,2]. Nevertheless, one can theoretically construct pathological examples with high treewidth.…”
Section: Treewidth and Treedepthmentioning
confidence: 99%
“…It is proven that structured programs in several languages, such as C, have bounded treewidth [78] and there are experimental works that establish small bounds on the treewidth of control-flow graphs of real-world programs written in other languages, such as Java [44], Ada [16] and Solidity [19]. Using these facts, [22] provides an ondemand algorithm with O(n • |D| 3 ) preprocessing time and O ⌈ |D| lg n ⌉ time per query 2 . In practice, |D| is often tiny in comparison with n and hence this algorithm is considered to have linear preprocessing and constant query time.…”
Section: Introductionmentioning
confidence: 99%
“…A similar approach is applied in [7] to retain the data blocks that are most wanted. Interestingly, the authors in [21] place data blocks based on the availability of cache memory in the server. A location-aware data block placement strategy for HDFS is devised in [22], by identifying virtual nodes' processing capacities in the cloud.…”
Section: Related Workmentioning
confidence: 99%